2017
DOI: 10.1111/jam.13360
|View full text |Cite
|
Sign up to set email alerts
|

Zeolite-based, dry formulations for conservation and practical application ofParaburkholderia phytofirmansPsJN

Abstract: This is the first study to provide ways of maintaining viability of PsJN during desiccation stress and to investigate the applicability of its EPS as a protectant, thus ultimately facilitating successful plant inoculation especially under field conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Evaluating a formulation regarding its viability during air‐drying is therefore highly relevant. Indeed, it has been reported that protectants working well for one drying method are not always suitable for another – as shown when developing dry formulations for P. phytofirmans (Berninger et al ., ). In this case, gum arabic and yeast extract maintained high survival rates during freeze‐drying, but not during air‐drying, whereas the opposite was true for mannitol.…”
Section: The Drying Processmentioning
confidence: 97%
See 3 more Smart Citations
“…Evaluating a formulation regarding its viability during air‐drying is therefore highly relevant. Indeed, it has been reported that protectants working well for one drying method are not always suitable for another – as shown when developing dry formulations for P. phytofirmans (Berninger et al ., ). In this case, gum arabic and yeast extract maintained high survival rates during freeze‐drying, but not during air‐drying, whereas the opposite was true for mannitol.…”
Section: The Drying Processmentioning
confidence: 97%
“…Particularly for non‐sporulating bacteria, which do not display the ability to adopt a highly resistant, dormant form to outlast adverse environmental conditions, desiccation is a physiologically challenging process (Potts, ). In extremely sensitive organisms, such as the endophytic plant growth‐promoting bacterium P. phytofirmans , desiccation coincided with a reduction in viability by six orders of magnitude (Berninger et al ., ). The damages resulting from desiccation partly depend on the drying method used, but are generally based on three main deleterious processes: oxidative damage, phase transition and browning reactions (García, ).…”
Section: Desiccation Damage and Protective Strategiesmentioning
confidence: 97%
See 2 more Smart Citations
“…3 ). Formulation can be solid-based or liquid, the former further can be either dry or wet as per the requirement ( Berninger et al, 2017 ; Oliveira et al, 2017 ; Berger et al, 2018 ).
Fig.
…”
Section: Commercial Biofertilizers: Preparation and Applicationmentioning
confidence: 99%